A Dating Style Student (Study of Symbolic Interaction Style Dating Students Graduate Program, University of Padjadjaran Bandung) - Sri Wahyuningsih (Communication Sphere, 2015)
ABSTRACT:Everyone in a relationship with someone definitely has a unique style of going out ontheir own. They interact with each other to know each other. This research took place in thecampus of the University of Padjadjaran, in order to determine how the student‟s style ofUniversity Padjadjaran is dating or in a relationship each other with the approach of SymbolicInteraction. Then bring out the constructs of observations and the results of in-depth interviewswith four informants as a student of S-2 program who again affair. 1) Construct romance stylewith sub-constructs: romantic love, love possess, love good friends, love pragmatic, altruisticlove, and love messing around. 2) Construct Factors associated with love is as follows rewards,gender differences and jealousy. 3) Construct Satisfaction and Commitment. 4) ConstructEnding Relationship.Keywords: Love Style, Symbolic Interaction, Love, Commitment